Recyclable ionic liquid iodinating reagent for solvent free, regioselective iodination of activated aromatic and heteroaromatic amines - Deshmukh, Amarsinh; Gore, Babasaheb; Thulasiram, Hirekodathakallu V.; Swamy, Vincent P. (RSC Advances, 2015)
This article describes a simple, efficient method for iodination of activated aromatic and heteroaromatic amines using recyclable 1-butyl-3-methylpyridinium dichloroiodate (BMPDCI) as an ionic liquid iodinating reagent, in the absence of any solvent. The main advantages are a simple efficient procedure, good yields and no need for any base/toxic heavy metals, or oxidizing agents. The ionic liquid was recovered and recycled in five subsequent reactions, without much loss of activity. This method was applied for the synthesis of the antiprotozoal drug iodoquinol and the antifungal drug clioquinol.

Ion pairing in 1-butyl-3-methylpyridinium halide ionic liquids studied using NMR and DFT calculations - Swamy, Vincent P.; Thulasiram, Hirekodathakallu V.; Rastrelli, Federico; Saielli, Giacomo (Physical Chemistry Chemical Physics, 2018)
We present the H-1, C-13 and N-15 NMR chemical shifts of bulk ionic liquids based on 1-butyl-3-methylimidazolium (the cation also known as 1-butyl-3-picolinium) halides (Cl-, Br- and I-) and tribromide (Br-3(-)) salts. A characterization in solution of the analogous ICl2- and I-3(-) salts is also reported. A series of DFT calculations has been run to predict the features of the NMR spectra of the pure ILs based on a few selected supramolecular ionic aggregates. To test the effect of temperature, and vibrational and conformational motions, only for the chloride salt, we also run first-principles molecular dynamics simulations of the ion pair in the gas phase, using the ADMP scheme (Atom Centered Density Matrix Propagation molecular dynamics model). The aim of our investigation is to test whether a simple DFT based approach of ion-pairing in ionic liquids is capable of providing reliable results and under which conditions the protocol is robust. We obtained a very good agreement between the calculated and experimental spectra for the three halides, where the bulk structure of the ILs is dominated by H-bond interactions between the X- anion (X = Cl, Br and I) and the ortho protons of the pyridinium ring (a structural arrangement not too different from the solid-state structure of pyridinium halides). In contrast, when the H-bond is weak, as in the Br-3(-) case, a number of supramolecular arrangements exist in solution and the simple DFT calculations of a few selected cases cannot exhaustively explore the complete energy landscape. Moreover, the dynamic effects due to thermal motion, evaluated by ADMP MD simulations of the chloride salt, appear to be not very significant.

Influence of the ion size on the stability of the smectic phase of ionic liquid crystals - Cao, Wudi; Senthilkumar, Beeran; Causin, Valerio; Swamy, Vincent P.; Wang, Yanting; Saielli, Giacomo (Soft Matter, 2020)
The thermotropic phase behavior of ionic liquids and ionic liquid crystals based on novel N-alkyl-3-methylpyridinium halides, trihalides and dichloroiodates was experimentally studied by polarized optical spectroscopy (POM) and differential scanning calorimetry (DSC) as well as by molecular dynamics (MD) simulation. In the experiments, the existence and thermal range of stability of the smectic phase of these ionic liquid crystals are found to strongly depend on the volume ratio between the cation and anion, that is their relative size. Only compounds with a relatively large volume ratio of the cation to anion, i.e., those with longer cationic alkyl chains and monoatomic halide anions, have a stable smectic A phase. Both melting points and clearing points increase with such a ratio. The MD simulation results qualitatively agree very well with the experimental data and provide molecular details which can explain the experimentally observed phenomena: the stronger van der Waals interactions from the longer alkyl chains and the stronger electrostatic interactions from the smaller anions with a higher charge density increase the stability of both the crystal phase and the smectic phase; this also prevents the ionic layers from easily mixing with the hydrophobic regions, a mechanism that ultimately leads to a nanosegregated isotropic liquid phase.